Defects Engineering Induced Ultrahigh Magnetization in Rare Earth Element Nd‐doped MoS2. Issue 2 (17th December 2020) - Ding, Xiang; Cui, Xiangyuan; Sohail, Ahmed; Murmu, Peter P.; Kennedy, John; Bao, Nina; Ding, Jun; Liu, Rong; Peng, Mingli; Wang, Lan; Chu, Xueze; Vinu, Ajayan; et al.
Abstract: Various concentrations (0, 0.5, 1, and 5 at%) of Nd are doped into MoS2 single crystals via ion implantation. Experimental results reveal that Nd exists in the form of trivalent state when the doping concentration is below 5 at% and a variety of defects, such as sulfur and molybdenum vacancies, are formed in Nd‐doped MoS2 . Compared to pure MoS2 that only shows diamagnetism, Nd doping successfully induces room‐temperature ferromagnetic ordering. Extremely high magnetization (1640 emu cm −3 ) is observed in 1 at% Nd‐doped MoS2 . First‐principles density functional theory calculations suggest that the various structural defects, including substitutions, vacancies, interstitials, antisites, and their complexes, are magnetic possessing large spin moments. The defects coupled with Nd dopants ferromagnetically may form the bound magnetic polarons to induce ferromagnetic ordering. The work has demonstrated that through defects engineering and rare earth element doping, extremely high magnetization materials can be achieved in layered structured materials. On the other hand, though the experiment work is done by implanting MoS2 single crystals, theoretical calculations indicate that 2D MoS2 with bilayers or a few layers can also result in ultrahigh magnetization. Abstract : Extremely high magnetization (1640 emu cm −3 ) is observed in 1 at% Nd‐doped MoS2 prepared by ion implantation. First‐principles calculations suggest that the various structural defects, including substitutions, vacancies, interstitials, antisites, and their complexes, are magnetic possessing large spin moments. The defects coupled with Nd dopants ferromagnetically may form the bound magnetic polarons to induce ferromagnetic ordering.